Influence of Transcutaneous Electrical Acupoint Stimulation on TLR4 Signaling Pathway-Related Factors in Patients with Diabetic Lower Extremity Vascular Disease - Dandan Sun; Yurui Li; Dou Zhang; Wei Wang; Guanghao Xia (Acupuncture & Electro-Therapeutics Research: International Journal of Integrated Medicine, 2026)
Objective: This study aims to examine the influence of transcutaneous electrical acupoint stimulation (TEAS) on clinical efficacy, lower extremity blood perfusion, and serum Toll-like receptor 4 (TLR4) signaling pathway-related factors in patients with diabetic lower extremity vascular disease. It also intends to explore potential mechanisms for improving lower-extremity ischemia and reducing inflammation. Methods: The study recruited a total of 145 patients with diabetic lower-extremity vascular disease admitted from January 2022 to December 2024, categorized into an observation group (73 cases) and a control group (72 cases) using the random number table method. Both groups were treated with standardized basic treatment, but the control group received additional cilostazol, while the observation group was additionally treated with TEAS. The two add-on regimens were directly compared on the same standardized background treatment. The treatment course lasted 8 weeks. The total clinical effective rate and ankle-brachial index (ABI), lower extremity arterial peak systolic velocity, vascular resistance index, transcutaneous oxygen pressure (TcPO 2 ) of the foot dorsum, serum TLR4, myeloid differentiation factor 88 (MyD88), nuclear factor- κ B p65 (NF- κ B p65), tumor necrosis factor- α (TNF- α ), interleukin-6 (IL-6), interleukin-1 β (IL-1 β ), high-sensitivity C-reactive protein (hs-CRP) and interleukin-10 (IL-10), hemorheology, blood lipids, and TCM syndrome score before and after treatment were compared between both groups. Results: The observation group obtained a higher total effective rate than the control group ( P < 0.05), and the distribution of the three efficacy grades differed between the groups ( Z = −2.510, P = 0.012). After treatment, increases in ABI, peak systolic velocity and TcPO 2 were observed for the observation group, while vascular resistance index decreased, all of which were superior to those in the control group ( P < 0.05). The observation group exhibited lower levels of serum TLR4, MyD88, NF- κ B p65, TNF- α , IL-6, IL-1 β , and hs-CRP as well as a higher level of IL-10 compared with those of the control group ( P < 0.05). Relative to the control group, levels of whole blood high-shear viscosity, plasma viscosity, fibrinogen, total cholesterol, and low-density lipoprotein cholesterol were lower for the observation group showed a greater reduction in the TCM syndrome score was better ( P < 0.05). Conclusion: TEAS can improve lower-extremity blood perfusion, relieve inflammatory response, and enhance clinical efficacy for patients with diabetic lower-extremity vascular disease. These effects were accompanied by decreases in serum TLR4, MyD88, and NF- κ B p65, indicating that the therapeutic effect of TEAS may be associated with the modulation of TLR4/MyD88/NF- κ B pathway-related serum factors.